Water Quality Characteristics of Lhok Geulumpang Estuary, Aceh Jaya - Sri Wahyuni; Asri Mursawal; Arung Samudra; Riki Saputra; Najam Rama; Tiara Andini; Meri Sartika (South East Asian Water Resources Management, 2026)
Water quality is a critical factor in determining the ecological condition of estuarine ecosystems, which are highly dynamic due to the interaction between freshwater and seawater. However, information on the water quality characteristics of the Lhok Geulumpang estuary in Aceh Jaya remains limited. This study aimed to analyze water quality parameters in the study area. Field measurements were conducted in October 2025 at a representative station using in situ methods. The observed parameters included temperature, salinity, pH, and dissolved oxygen (DO), with three replicates for each measurement. The collected data were analyzed descriptively and compared with environmental quality standards. The results showed that water temperature ranged from 29.8 to 30.0°C, salinity from 7.24 to 9.39 ppt, pH from 7.61 to 8.31, and DO from 4.3 to 4.9 mg/L. These values indicate that the study area exhibits typical estuarine characteristics, particularly reflected by low salinity due to freshwater influence. The results indicate that the Lhok Geulumpang estuary is in relatively good condition and can support aquatic life. However, the slightly lower DO concentration suggests the need for continuous monitoring to ensure long-term environmental sustainability